Repositioning The “Holy Remnant” of Israel: German Jewish Negotiations with Christian Culture on the Eve of the Holocaust - Krell, Marc A. (Studies in Christian-Jewish Relations, 2011)
By maintaining the spiritual centrality of Israel as God’s “holy remnant,” Dietrich Bonhoeffer, unwittingly perhaps, entered into negotiations with Jewish thinkers over their continued theological and cultural relevance to German society. This paper focuses on the Jewish side of these negotiations by examining the work of three Jewish thinkers who helped shape them, Franz Rosenzweig, Hans Joachim Schoeps and Martin Buber. Despite their divergence from one another, the theological approaches of Rosenzweig, Schoeps and Buber represent a common attempt to map out the course of twentieth-century Jewish identity construction based on a shared, but at times unacknowledged engagement with Christian thought and culture. Their writings constitute a mutual opposition to the perceived failure of their forbearers in the Wissenschaft des Judentums to balance Jewish particularity and universalism, while at the same time reflecting a desire for varying degrees of mutual coexistence with their Christian contemporaries. Ultimately the work of Rosenzweig, Schoeps and Buber confirmed Bonhoeffer’s portrayal of the continuing validity of Jewish existence in relation to God during the Holocaust, while at the same time providing models for a later, dialogical mapping of Jewish identities vis à vis Christianity in an increasingly multicultural, post-Holocaust world.